Pengaruh Variasi Waktu Sputtering Terhadap Karakteristik Mekanik dan Evolusi Struktur Mikro Baja AISI 4140 - Niki Agastia Mutaqin; Amarullah (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
AISI 4140 steel is a high‑strength, low‑alloy material commonly used in mechanical components subjected to high load and friction. Although its bulk properties are favorable, surface modification is often required to enhance wear resistance and prolong service life. This study investigates the influence of DC sputtering Titanium Nitride (TiN) deposition time on the mechanical performance and microstructural evolution of AISI 4140 steel. The experimental procedure varied sputtering times at 30, 60, 90, 120, and 150 minutes while maintaining constant processing parameters. Characterization techniques included Vickers hardness testing, wear testing, and SEM–EDX analysis to evaluate coating morphology and coating–substrate interface quality. The results indicate that TiN deposition significantly enhances surface hardness compared to the uncoated substrate. The maximum hardness value of 186.66 VHN was achieved at 60 minutes of deposition, corresponding to a dense, uniform coating with strong adhesion. Prolonged deposition times, however, led to decreased hardness and increased wear rate, attributed to excessive coating thickness, microstructural non-uniformity, and the formation of micro-defects. SEM observations corroborate these findings by revealing notable variations in coating morphology and interface integrity across deposition durations. Overall, the study concludes that sputtering time is a critical parameter in optimizing TiN coatings to improve the surface performance of AISI 4140 steel for engineering applications.